Influence of diffusion on the resolution of a multi-channel electrical mobility analyzer - Panich Intra (2018)
A long multi-channel electrical mobility analyzer (long MCEMA) has been developed and presented for classifying and measuring the size distribution of aerosol particles in the range of 10 to 1000 nm (Intra and Tippayawong, 2009, 2011). In the idealized model, when there are no molecular and no turbulent diffusion, the charged particles in the MCEMA move along precisely determined trajectories, and the apparatus gives the undistorted mobility spectrum. Here we neglect the effect of the finite width of aerosol inlet channel and of the finite width of the electrometer rings. Practically, however, molecular and turbulent diffusion randomly scatters the trajectories of the particles, giving a smoothed mobility spectrum. The degree of smoothing can be characterized by the resolution. The resolution of the MCEMA can be expressed by an analytical equation because molecular diffusion submits itself relatively well to a theoretical description. Because of the complexity of turbulent diffusion, simplifying assumptions were made for this work. The MCEMA resolution values were calculated based on expected turbulence parameter data. An increase in the inner electrode voltage resulted in an increase in the resolution of the mobility spectrometer. Higher electrometer ring numbers were found to have higher resolution values of the long MCEMA than the lower electrometer ring numbers. The resolution R d for the electrometer ring number 22 was found to be as high as 150, 280, and 550 for inner electrode voltages of 1, 2, and 3 kV, respectively. The influence of Brownian diffusion on the resolution of the long MCEMA was significant for particles smaller than 100 nm, corresponding to electrometer ring numbers lower than 10. Approximate calculations show that the mobility resolution decreased considerably even with low turbulence in the classifier. © 2013 Copyright Taylor and Francis Group, LLC.